Video games and children’s books in translation - Bernal, Miguel (The Journal of Specialised Translation, 2009)
The young and the not-so-young have enjoyed reading what we now call children’s books for many decades. Be it a comic book or a novel, this type of literature often captivates us with its fantastic worlds and magical characters, but what happens to these popular books when they get turned into video games? The change of medium implies the reworking of the original source into a different format that will, ideally, combine the creative charm of the old content and the thrill of the new multimedia interactive technology in a way that is agreeable to both. Then, the difficulties of translating literature and entertainment software combine in the same product, raising a series of new issues to the localisation industry, language service professionals, and translation studies. This article proposes an initial polysystem where video games and children’s books can be studied for their creative value, and this is directly relevant to the degree of creativity and amount of research that the translation of these multimedia interactive entertainment software products for foreign locales require. Hopefully this will open new areas of research within translation studies.